COLOUR - PENCIL DRAWING : TECHNIQUES AND TUTORIALS FOR THE COMPLETE BEGINNER - Ferreira, Kendra; Morris, Lisa (Lewes, East Sussex, UK : Guild of Master Craftsman Publications Ltd., 2019)
Learn how to draw with colored pencils by following this easy and accessible guide, in which award-winning artist Kendra Ferreira demonstrates the creative potential of an exciting and highly versatile artistic medium. Colored pencils combine the expressivenessof painting with the control of drawing. They allow for really rich and luminous color, with finished drawings being so detailed and pigmented that they resemble paintings. --Publisher
Includes index
Keywords: Colored pencil drawing -- Technique